2004
DOI: 10.1023/b:myco.0000041892.26907.b4
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Aflatoxins in Herbal Medicinal Products in Thailand

Abstract: Twenty-eight herbal medicinal products from Thailand were investigated for aflatoxin (AF) contaminations by employing a specific HPLC assay for the determination of AFB1, B2, G1 and G2. The samples were extracted with 80% (v/v) methanol in water before further cleaned up with an immunoaffinity column and followed by the detection of AFs by using an electrochemically post-column derivatization with iodine and fluorescence detector. The extraction procedure was optimized in order to obtain the best recovery. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 9 publications
5
44
1
1
Order By: Relevance
“…The results showed that 54.9% of the samples exceeded the limit determined by the US Pharmacopoeia (26) and these results are in agreement with those of previous studies (16)(17)(18)21,25 4 cfu/g) were the most contaminated samples. According to plant part used, the highest counts of fungal isolates were observed in leaves and aerial parts (50.0%) followed by flowers (16.0%), rhizomes and roots (12.0%), barks (12.0%) and seeds (10.0%).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results showed that 54.9% of the samples exceeded the limit determined by the US Pharmacopoeia (26) and these results are in agreement with those of previous studies (16)(17)(18)21,25 4 cfu/g) were the most contaminated samples. According to plant part used, the highest counts of fungal isolates were observed in leaves and aerial parts (50.0%) followed by flowers (16.0%), rhizomes and roots (12.0%), barks (12.0%) and seeds (10.0%).…”
Section: Resultssupporting
confidence: 91%
“…The premise that traditional use of these medicinal products for generations establishes their safety does not necessarily attest to their safety and efficacy. Indeed, the adverse effects of long-term herbal use, adulteration with toxic compounds and contamination by pathogenic microbials or natural toxins like mycotoxins have been reported for herbal products and medicinal plants (1,2,(7)(8)(9)(10)(11)13,(16)(17)(18)(19)(20)(21)(22)25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devido a sua especificidade, o emprego de coluna de imunoafinidade atualmente está bem difundido em diferentes tipos de alimentos, como café, cerveja, leite, queijo, suco de maçã, iogurte e matrizes complexas como salsa e plantas medicinais. [20][21][22][23][24][25][26][27][28][29][30][31] O objetivo desse trabalho foi avaliar o grau de contaminação com aflatoxina B 1 em amostras de pimenta (Piper nigrum L.) e orégano (Origanum vulgare L.) comercializadas no estado de Minas Gerais. Inicialmente, foram avaliados alguns parâmetros de um método analítico, utilizando extração com metanol-água, purificação em coluna de imunoafinidade e detecção e quantificação da aflatoxina B 1 por cromatografia em camada delgada/densitometria.…”
Section: Introductionunclassified
“…However, in order to improve detection limits of AFB 1 and AFG 1 , a tedious pre-or postcolumn derivatization must be done in conventional HPLC methods Tassaneeyakul et al, 2004). These problems have been successfully solved in the present study by introducing HPLC-MS method.…”
Section: Hplc-ms-msmentioning
confidence: 99%